USING INFORMATION TRANSFER DIAGRAM ACTIVITY IN TEACHING LISTENING COMPREHENSION - Jaya, Aswadi (Jurnal Smart, 2021)
The reason to use the information transfer is that the students not only focus to listen but also to transfer the point what they hear. The main problem of this study wasâ€œIs it effective to teach listening by using information transfer diagram activity to the seventh-grade students?â€ The method of research used in this study was the pre-experimental method. Based on the result of the data analysis, it was found that teaching listening by using information transfer diagram activity to the seventh-grade students.